Character Education and Ethical Development: A Bibliometric Study of Youth Education - Loso Judijanto; Eko Nursalim; Ratna Ayu Pawestri Kusuma Dewi; Nasruddin Nasruddin; Nur Wahyuning Sulistyowati (West Science Social and Humanities Studies, 2024)
This study employs a bibliometric analysis to explore the scholarly landscape of character education and ethical development, focusing on trends, influential contributors, and emerging themes from 2000 to 2024. Using Scopus database, the study identifies key research areas such as moral education, virtue ethics, and interdisciplinary connections with fields like psychology, philosophy, and technology. The findings highlight the centrality of foundational figures such as Kohlberg and Dewey, while emerging themes like artificial intelligence, e-learning, and sustainable development reflect the field's evolving focus. The analysis reveals geographic disparities, with the United States as a dominant contributor, and emphasizes the need for culturally inclusive approaches. Despite advancements, challenges remain in the variability of program implementation, lack of longitudinal studies, and ethical considerations in technology integration. This study provides valuable insights for researchers, educators, and policymakers to advance the field and address contemporary ethical challenges in education.